2020
DOI: 10.1038/s41398-020-01014-x
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian target of rapamycin (mTOR) kinase mediates haloperidol-induced cataleptic behavior

Abstract: The mammalian target of rapamycin (mTOR) is a ubiquitously expressed serine/threonine kinase protein complex (mTORC1 or mTORC2) that orchestrates diverse functions ranging from embryonic development to aging. However, its brain tissue-specific roles remain less explored. Here, we have identified that the depletion of the mTOR gene in the mice striatum completely prevented the extrapyramidal motor side effects (catalepsy) induced by the dopamine 2 receptor (D2R) antagonist haloperidol, which is the most widely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 62 publications
(60 reference statements)
3
20
0
Order By: Relevance
“…These results are in line with observations from the real-time metabolic assays, although all antipsychotics lowered the expression of iNOS, indicating a different mechanism for metabolic reprogramming between the tested antipsychotics. Recent studies have shown that haloperidol has capabilities in increasing mTORC1 activity in neurons, which was also linked to extrapyramidal motor side effects [57][58][59]. Increased mTORC1 activity and glycolysis was also seen in olanzapine [60], a second-generation antipsychotic, similar to what we found in cells treated with risperidone.…”
Section: Discussionsupporting
confidence: 86%
“…These results are in line with observations from the real-time metabolic assays, although all antipsychotics lowered the expression of iNOS, indicating a different mechanism for metabolic reprogramming between the tested antipsychotics. Recent studies have shown that haloperidol has capabilities in increasing mTORC1 activity in neurons, which was also linked to extrapyramidal motor side effects [57][58][59]. Increased mTORC1 activity and glycolysis was also seen in olanzapine [60], a second-generation antipsychotic, similar to what we found in cells treated with risperidone.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, in the catalepsy test, metformin significantly reduced the latency of descent from the bar in all tests performed, regardless of the time. These results are in agreement to those previously presented by Adedeji et al [33], that metformin reduces the period of immobilization and improves the ability of behavioral adaptation [34].…”
Section: Discussionsupporting
confidence: 94%
“…Western blotting from striatal tissue were carried as described before [78, 79] . Striatal tissue was rinsed briefly in PBS and directly lysed in lysis buffer [50 mM Tris-HCl (pH 7.4), 150 mM NaCl, 1% Triton X-100, 1x protease inhibitor cocktail (Roche, Sigma) and 1x phosphatase inhibitor (PhosStop, Roche, Sigma)], sonicated for 2 x 5 sec at 20% amplitude, and cleared by centrifugation for 10 min at 11,000 g at 4°C.…”
Section: Methodsmentioning
confidence: 99%